Individual student support and counselling for undergraduate pharmacy students at an historically disadvantaged institution - Lindi Angeline Mabope; Beverley Summers; Anna-Marie Wium; Johanna Meyer (Journal of Student Affairs in Africa, 2025)
Many students who meet higher education admission standards struggle in their respective programmes because they lack the necessary skills and/or abilities to navigate complex institutions of higher education. This study aimed to determine individual counselling's role in pharmacy students' academic performance in a problem-based learning (PBL) programme at a South African University. Students identified as “at-risk” of failing were the focus, and the study was retrospective, cross-sectional and quantitative. This article presents possible individualised remedial measures that can be applied to reduce the attrition rate and stimulate success among a diverse student body in the BPharm programme. Early monitoring and evaluation of students “at-risk” of failing from across all year groups ensure the long-term success of activities and plans in a diverse atmosphere, effectiveness, efficiency, and accountability to the stakeholders.